1994
DOI: 10.1002/zaac.19946200712
|View full text |Cite
|
Sign up to set email alerts
|

Synthese, Struktur und Reaktivität von Bis(dialkylamino)diphosphanen

Abstract: Ausgehend von den Aminochlorphosphanen iPr2NPCl2 1 und (iPr2N)2PCl 2 wird die Synthese neuer funktionalisierter Aminophosphane (iPr2N)2PSiMe3 3a, (iPr2N)2PSnMe3 3b, (iPr2N)(DMP)PCl 4, iPr2NP(SiMe3)2 5 und iPr2NP(SiMe3)Cl 6 beschrieben. Durch Umsetzung von 2 mit verschiedenen Phosphiden erhält man die Aminodiphosphane (iPr2N)2PP(SiMe3)2 7a, (iPr2N)2PP(SiMe2tBu)2 7b, (iPr2N)2PPPh2 8 und (iPr2N)2PPH2 9. Die Phosphane 3a/b reagieren mit Halogenphosphanen zu den Aminohalogendiphosphanen (iPr2N)2PPCl2 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
2
22
0
6
Order By: Relevance
“…Im Gegensatz zu den bei Diphosphanen vor herrschenden gauche-oder /ra«s-Anordnungen der Substituenten stimmt diese K onform ation eher mit "Empirical force field"-Berechnungen für Diphosphane mit sterisch anspruchsvollen Ligan den überein, die eine halbekliptische K onform a tion Vorhersagen [23], Dies konnte bereits anhand von Strukturuntersuchungen einiger alkyl-, silylund am inosubstituierter D iphosphane (r = 5-30°) [11,24] verifiziert werden.…”
Section: Kristallstruktur-bestimmungenunclassified
“…Im Gegensatz zu den bei Diphosphanen vor herrschenden gauche-oder /ra«s-Anordnungen der Substituenten stimmt diese K onform ation eher mit "Empirical force field"-Berechnungen für Diphosphane mit sterisch anspruchsvollen Ligan den überein, die eine halbekliptische K onform a tion Vorhersagen [23], Dies konnte bereits anhand von Strukturuntersuchungen einiger alkyl-, silylund am inosubstituierter D iphosphane (r = 5-30°) [11,24] verifiziert werden.…”
Section: Kristallstruktur-bestimmungenunclassified
“…The P1ÀP2 bond length in 5 a (2.334(1) , Figure 1) is substantially longer than typical PÀP distances in diphosphanes (2.217 AE 0.08 [8] ) and exceeds even the distances in the sterically overcrowded [{(Me 3 Si) 2 CH} 2 P] 2 (2.310 ), [9] which dissociates easily under homolytic cleavage of the PÀP bond to give two radicals, and in the 1,1-diaminodiphosphane (iPr 2 N) 2 PÀPPh 2 (2.250 ), [10] for which, owing to the significantly lower cation stability of (iPr 2 N) 2 P + as compared to a diazaphospholenium cation, [3] a less pronounced dipolar polarization of the PÀP bond is expected.…”
mentioning
confidence: 99%
“…The syntheses of 1 and 2 were conducted according to Domańska-Babul et al, 5 the synthesis of 3 similarly to King and Sundaram, 6 and the synthesis of 4 similarly to Bender et al 7 We obtained a much higher yield of 4 than previously reported, probably because we used the isolated ( i Pr 2 N) 2 P-P(SiMe 3 )Li (2), and the synthesis was conducted at temperatures not higher than 20 • C. Moreover, we have found that, even at room temperature, ( i Pr 2 N) 2 P-P(SiMe 3 )Li undergoes a slow decomposition leading to the formation of phosphetanes and polyphosphorus compounds. 5 We studied the reactivity of 4 towards BuLi in THF solution in order to obtain the related lithium compound ( i Pr 2 N) 2 P-P(Li)-P(N i Pr 2 ) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…12 The P1-P2 distance of 224.03(13) pm is in the range of a P-P single bond, and the P-Si distance 225.97(14) pm (mean) is typical for a P-Si single bond. The coordination around the phosphorus atoms P1 and P2 is tetrahedral, with the sum of angles around these phosphorus atoms being 332.00(6) deg and 321.39 (12) deg, respectively. The arrangement around N1 and N2 is almost planar; the sum of angles around N1 is 359.5(2)deg and around N2 is 356.7(2) deg.…”
Section: Crystal Data Measurement Conditions and Refinement Parametmentioning
confidence: 99%
See 1 more Smart Citation